1991
DOI: 10.1172/jci115391
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil accumulation in the lung in alpha 1-antitrypsin deficiency. Spontaneous release of leukotriene B4 by alveolar macrophages.

Abstract: The emphysema of al-antitrypsin (alAT) deficiency is concep-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 60 publications
6
124
0
2
Order By: Relevance
“…MPO concentrations were higher, as was the chemoattractant LTB 4 . This suggests that LTB 4 may be the major chemoattractant responsible for the increased neutrophil migration and is consistent with previous findings in bronchoalveolar lavage [33]. The source of the LTB 4 is uncertain although HUBBARD et al [33] suggested that it was released from alveolar macrophages as a direct effect of uninhibited elastase due to a 1 ATD.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…MPO concentrations were higher, as was the chemoattractant LTB 4 . This suggests that LTB 4 may be the major chemoattractant responsible for the increased neutrophil migration and is consistent with previous findings in bronchoalveolar lavage [33]. The source of the LTB 4 is uncertain although HUBBARD et al [33] suggested that it was released from alveolar macrophages as a direct effect of uninhibited elastase due to a 1 ATD.…”
Section: Discussionsupporting
confidence: 86%
“…This suggests that LTB 4 may be the major chemoattractant responsible for the increased neutrophil migration and is consistent with previous findings in bronchoalveolar lavage [33]. The source of the LTB 4 is uncertain although HUBBARD et al [33] suggested that it was released from alveolar macrophages as a direct effect of uninhibited elastase due to a 1 ATD. Indeed, in the current study elastase activity was more readily detected in the a 1 ATD patients irrespective of bacterial colonization and hence would support the suggestion that this may be responsible [33].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…LTB 4 is a potent PMN chemoattractant and stimulates PMN to release elastase and generate superoxide radicals [5,36,47]. The role of LTB 4 in promoting self-perpetuating inflammatory injury at various mucosal surfaces is well established [17,19,41]. Although PMN are the principal source of LTB 4 in the bovine lung infected with M. haemolytica [8,18] the direct effects of tilmicosin on LTB 4 synthesis by bovine PMN remain incompletely understood.…”
Section: In Pmnmentioning
confidence: 99%
“…Furthermore, because NE can stimulate the release of cathepsin B and matrix metalloprotease-2 from macrophages [ 119 ], this can exacerbate lung damage as the resulting degradation products are found to have a chemotactic effect for monocytes [ 120 ]. NE also upregulates the release of chemotactic mediators such as leukotriene B4 [ 121 ] and IL-8 [ 122 ], which leads to an increased concentration of neutrophils in the bronchoalveolar lavage (BAL) of AATD patients [ 40 , 42 , 97 , 123 ]. Thus, the extracellular protease-antiprotease imbalance triggers a cascade of proteostasis mismanaged destruction of alveolar wall that causes defective alveoli (Fig.…”
Section: Aatd Proteostasis and Lung Diseasementioning
confidence: 99%